Comparative studies on Non-Divergent Load flow methods in well, ill and unsolvable condition - Shahriari, Amidaddin; Bakar, Ab Halim Abu; Mokhlis, Hazlie (IEEE, 2010)
This paper describes a critical evaluation of NonDivergent Load flow methods in well, ill and unsolvable conditioned systems. The comparison studies deals Multiple Load Flow Solution (MLFS) based Second-Order Load-Flow (SOLF) in polar coordinate and Continuation Load Flow (CLF). The analytical bases, ability consideration of theses methods to return operation of power system from unsolvable to solvable region solution. Attention is given to the problems and techniques of to provide optimal recommendations of the parameters, that using in these Non-Divergent Load flow methods to lead to solvable region, based on inequality constraints of power system. A part of the survey, this paper also presents the comparison of numerical result using different type of aforesaid load flow methods for well and iII- conditioned systems. Accordingly, load flow simulation has been solved using the C++ programming.